Current practice in pharmacy education: inter-and intra-country comparisons of the pharmacy practice syllabus / Mohd. Ghazali Ismail - Ismail, Mohd. Ghazali (2006)
Pharmacy education covers wide scope of study and Pharmacy Practice is one of the components. This project was conducted to make a comparison between the Pharmacy Practice syllabi from 6 established Universities. The purposes of this project were to determine the similarities and differences of Pharmacy Practice syllabi structured within the selected universities. Using direct head-to-head comparison, Pharmacy Practice syllabi from selected universities were directly compared and the relevant, matching sub-topics were analyzed. Three aspects were screened; including the similarities of syllabi components, the differences of syllabi components, and the evaluation format conducted during learning assessment. The data were presented in table form as percentage of course work to written examination ratio. In terms of similarity, all the universities offered Pharmacy Practice syllabi which consist of dispensing, manufacturing and compounding skills, sterile production management, and community and hospital Pharmacy Practice as core components. However, no standard nomenclatures were given to all Pharmacy Practice-related courses stated in Pharmacy degree curricula of the respective universities. Two approaches were used as Pharmacy Practice syllabi instrument to evaluate students performance; course work and written examination. Traditionally, written examination was given higher priority as compared to course work in term of assessment ratio. In addition to that, every university had specific format to evaluate the students. However, the justification of use of such approaches was not cleared. A comprehensive study should be conducted to design a standard for Pharmacy Practice syllabi that can be used for all universities worldwide.